The relationship between service customers' quality assurance behaviors, satisfaction, and effort: A cost of quality perspective - Youngdahl, William E.; Kellogg, Deborah L. (Journal of Operations Management, 1997)
Abstract The overarching purpose of this article is to deepen understanding of customers' roles in service quality assurance. Customers engage in quality assurance behaviors in attempts to increase their satisfaction and to recover from service failures. The non‐monetary costs incurred by customers who engage in these behaviors represent largely overlooked costs of quality that can and should be factored into service design and management. Four customer costs of service quality are identified using a critical incident methodology to classify service customers' quality assurance behaviors. Then, relationships between customers' quality assurance behaviors and reported levels of effort and satisfaction are tested to better understand the implications of the typology. Finally, we provide some initial suggestions for integrating the quality assurance behaviors of customers with the service management activities of service providers.